Cigarette Smoke Exposure-Associated Alterations to Non-Coding RNA - Maccani, Matthew A.; Knopik, Valerie S. (Frontiers in Genetics, 2012)
Environmental exposures vary by timing, severity, and frequency and may have a number of deleterious effects throughout the life course. The period of in utero development, for example, is one of the most crucial stages of development during which adverse environmental exposures can both alter the growth and development of the fetus as well as lead to aberrant fetal programming, increasing disease risk. During fetal development and beyond, the plethora of exposures, including nutrients, drugs, stress, and trauma, influence health, development, and survival. Recent research in environmental epigenetics has investigated the roles of environmental exposures in influencing epigenetic modes of gene regulation during pregnancy and at various stages of life. Many relatively common environmental exposures, such as cigarette smoking, alcohol consumption, and drug use, may have consequences for the expression and function of noncoding RNA (ncRNA), important post-transcriptional regulators of gene expression. A number of ncRNA have been discovered, including microRNA (miRNA), Piwi-interacting RNA (piRNA), and long noncoding RNA (long ncRNA). The best-characterized species of ncRNA are miRNA, the mature forms of which are 22 nucleotides in length and capable of post-transcriptionally regulating target mRNA utilizing mechanisms based largely on the degree of complementarity between miRNA and target mRNA. Because miRNA can still negatively regulate gene expression when imperfectly base-paired with a target mRNA, a single miRNA can have a large number of potential mRNA targets and can regulate many different biological processes critical for health and development. The following review analyzes the current literature detailing links between cigarette smoke exposure and aberrant expression and function of noncoding RNA, assesses how such alterations may have consequences throughout the life course, and proposes future directions for this intriguing field of research.